Women studying and working in engineering : case studies from UCT and civil engineering in the Western Cape - Conrad, Ashraf (Department of Sociology, 2023)
In this thesis two case studies were used to investigate women's involvement in engineering in the Western Cape during the early to mid 1990s. The first study provided a statistical profile of women engineering students (WES) at UCT as background to the second, a qualitative, in-depth study that used life-story interviews to identify experiences and attitudes of professional women civil engineers (WE). In 1993, data on demographics, school and social background, reasons for doing engineering and diversity life of WES was collected in sections, by academic year, by groups of senior undergraduate Sociology research students for their individual final year research projects. The questionnaire they used was standardized and contained both closed and open-ended questions. The analysis in this thesis of the WES database combined the data from the different individual Sociology research projects, culminating in a 70% (59 of 83) sample of 2nd, 3"1, 4th and postgraduate year white, coloured and Indian women students registered at UCT in 1993. The results of this analysis showed that the majority of U CT students in the early 1990s were white, young, single women. By using data about parents education levels (50% of mothers and 75% of fathers had received some form of further or higher education) and parents occupations (two-fifths of the mothers and more than half of the fathers held qualified positions) they were fowid to be socially privileged. Individually, and as a group, their performance at school was outstanding, with the entire group achieving an A- or B- matric aggregate with many showing a clear preference for mathematics and science. Using a framework of categories refmed by Jawitz and Case (1998), three categories of reasons for doing engineering, namely "Socialisers" (including having an engineer in the family), "Contact with Engineering" (through open days organised by educational institutions or engineering organisations) and performance and ability in "School Subjects", were fowid to be particularly significant. Isolated incidents of sexist attitudes from male colleagues and lecturers did not detract from an overall positive attitude to studying engineering by the WES, as evidenced by nearly 90% willing to conditionally or wiconditionally support, over opposing, or not recommending, the decision by other women to do engineering. The transcription of audio-taped life-story interviews, conducted in 1998 and 1999, with Cape Town-based women civil engineers provided the qualitative data of the WE study. In the analysis, resistance to entry by women to, and the creation of an wiwelcome atmosphere for women on the building site, came strongly to the fore. Also, some women encowitered serious incidents of sexual harassment and gender discrimination on the building site and even in the office environment. The existence of women's engineering organizations were fowid to partly fill the need for women to network and support each other in the face of a hostile environment in traditional male-dominated industries. The conflicting demands of motherhood and career were fowid to exact a heavy physical and emotional toll on professional women. These women, however, negotiated this conflict in coming. up with Wlique, specialised and livable solutions.